2016
DOI: 10.3389/fnagi.2016.00108
|View full text |Cite
|
Sign up to set email alerts
|

In Alzheimer’s Disease, 6-Month Treatment with GLP-1 Analog Prevents Decline of Brain Glucose Metabolism: Randomized, Placebo-Controlled, Double-Blind Clinical Trial

Abstract: In animal models, the incretin hormone GLP-1 affects Alzheimer’s disease (AD). We hypothesized that treatment with GLP-1 or an analog of GLP-1 would prevent accumulation of Aβ and raise, or prevent decline of, glucose metabolism (CMRglc) in AD. In this 26-week trial, we randomized 38 patients with AD to treatment with the GLP-1 analog liraglutide (n = 18), or placebo (n = 20). We measured Aβ load in brain with tracer [11C]PIB (PIB), CMRglc with [18F]FDG (FDG), and cognition with the WMS-IV scale (ClinicalTrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
272
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 329 publications
(283 citation statements)
references
References 46 publications
(64 reference statements)
9
272
0
2
Order By: Relevance
“…Any means to reinstate the homeostatic regulation between Tau and insulin signalling can then be considered of therapeutic interest. This could be directly achieved by activating IRs or targeting downstream pathways using PTP1B inhibitors [221], GLP-1 receptor agonists [162, 222, 223], or intranasal insulin administration [224, 225]. Alternatively, one could imagine that strategies aimed at clearing pathological forms of Tau (such as Tau immunotherapy) [226, 227] could allow reestablishment of proper brain insulin signalling.…”
Section: Resultsmentioning
confidence: 99%
“…Any means to reinstate the homeostatic regulation between Tau and insulin signalling can then be considered of therapeutic interest. This could be directly achieved by activating IRs or targeting downstream pathways using PTP1B inhibitors [221], GLP-1 receptor agonists [162, 222, 223], or intranasal insulin administration [224, 225]. Alternatively, one could imagine that strategies aimed at clearing pathological forms of Tau (such as Tau immunotherapy) [226, 227] could allow reestablishment of proper brain insulin signalling.…”
Section: Resultsmentioning
confidence: 99%
“…The drug liraglutide has been shown to protect the brain from the AD disease progression in an 18 FDG-PET imaging study. The AD typical reduction of brain activity and energy utilization was prevented by liraglutide, indicating that the drug reversed the IR in the brain and normalized brain function (Gejl et al, 2016). A phase II clinical trial is currently ongoing (Holscher, 2014a).…”
Section: Effects Of Glp-1 On Neurodegenerative Diseasementioning
confidence: 98%
“…In a 6-month double-blinded trial, liraglutide produced increased cerebral metabolism of glucose versus placebo in multiple regions of interest [7], although the study was not powered to detect clinical outcomes. In an open-label study in 19 patients with comorbid affective disorder, 4 weeks of liraglutide was associated with improvements in multiple cognitive domains, although the study was uncontrolled [10].…”
Section: Liraglutidementioning
confidence: 99%
“…However, as only three studies reported such data [6][7][8], all with varying study populations, meta-analysis was not performed.…”
Section: Meta-analysismentioning
confidence: 99%